Supplementary Material for: Trait-like and State-like Oxytocin: A Biomarker of Alliance in Patients with Depression and Borderline Personality Disorder - figshare admin karger (2628495) (2025)
Introduction: Patients with Major depressive disorder (MDD) and Borderline personality disorder (BPD) show a poorer prognosis compared to patients without BPD. A potential contributor is the complexity of establishing a therapeutic alliance with patients with BPD. A potential underlying biological mechanism is Oxytocin (OT), a hormone associated with social bonding and trust. The aim of this study was to assess whether the interaction between OT pre-session (session-level trait-like) and change in OT throughout session (state-like) in both patients and therapists predicts the therapeutic alliance in patients with MDD and varying severity of BPD. We hypothesized that patients with higher BPD severity would show a compensatory pattern, where increase in state-like OT would compensate for low session-level trait-like OT, resulting in a stronger alliance. We also explored this interplay in the therapists' OT. Method: Eighty-four patients from a randomized control trial were assessed for BPD severity prior to beginning 16 sessions of short-term psychotherapy. Both patients and therapists provided saliva samples pre- and post- sessions 4, 8, 12 and 16 for OT analysis. Alliance was measured post-session. A series of linear mixed-effects models was used to test the hypothesis. Results: Our hypothesis was partially confirmed. In patients with higher BPD severity, when therapists had low session-level trait-like OT, the more they increased in state-like OT, patients rated their alliance as stronger. However, this compensatory pattern did not emerge in patients. Conclusion: These findings demonstrate the potential importance of OT as a biomarker of therapeutic processes in patients with MDD and BPD.